دراسة كفاءة استخدام المياه باختلاف معاملات الري بالرش على بعض الصفات الانتاجية للذرة الصفراء (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
The research was conducted at Sit Kheris Agricultural Station in Latakia Agriculture Center, General Commission for Scientific Agricultural Research (GCSAR) in Syria, during the season 2018. The maize variety (Gasper) was used. Three levels of irrigation were applied (70, 80, and 90%) of the total water need of plant in addition to the control (100%). The experiment excuted according to Randomized Complete Block Design (RCED) with three replicates. Evapotranspiration values (ETo) were calculated by (Eto calculator ) program and the evaporation values of Class A Basin which were periodically taken in order to study the efficiency of water use efficiency, water  consumption and scheduling crop irrigation, in addition to the study of the effect of spraying irrigation treatments on some of the yield characteristics of the maize.                The results showed a strong positive correlation, between the values of the evapotranspiration reference (Eto) calculated by (Eto calculator) program and the evaporation values from Class A basin (r = 0.9508), the maximum value of the total water consumption of the plant in the Flowering stage, and the least during germination, This is what facilitates the use of ETo in the required modeling. The difference of irrigation treatments in their effects on the productive properties of maize with a significant and large advantage of irrigation treatment 80% of the total water need and significantly on other irrigation treatments, especially on the grain yield characteristics and the number of grains in grade and their number in the corn cob. The superiority of the two irrigation treatments 70% and 80% with significantly (4.52 – 4.48 kg/m3 ) respectively in water efficiency and  refinement rate (46.21 – 42.77 %) respectively.   نفذ هذا البحث في محطة ستخيرس الزراعية في محافظة اللاذقية التابعة للهيئة العامة للبحوث العلمية الزراعية في سورية, خلال الموسم 2018 على صنف الذرة الصفراء Zea mays L. كاسبر، حيث طبقت ثلاثة مستويات من الري بالرذاذ (90-80-70 %) من الاحتياج المائي الكلي للنبات بالإضافة للشاهد (100%) بتصميم القطاعات العشوائية الكاملة (RCBD) وبثلاثة مكررات. استخدمت قيم التبخر النتح المرجعي (ETo) المحسوبة ببرنامج ETo calculator وقيم التبخر من حوض Class A المتبعة بشكل دوري ودرست العلاقة بينهما, وذلك بهدف دراسة كفاءة استخدام المياه, وكمية الاستهلاك المائي, وجدولة عملية الري للمحصول، وتأثير معاملات الري بالرش على بعض الصفات الانتاجية لصنف الذرة الصفراء. أظهرت النتائج وجود علاقة ارتباط موجبة وقوية بين قيم التبخر نتح المرجعي (ETo) المحسوبة باستخدام برنامج ETo Calculator وقيم التبخر من حوض Class A (r2=0.9508)، وأكبر كمية للاستهلاك المائي الكلي للنبات في طور الإزهار, وأقلها في فترة الانبات وهذا مايسهل استخدام ETo بالنمذجة المطلوبة. اختلفت معاملات الري في تأثيرها على الصفات الانتاجية للذرة الصفراء مع تميز كبير وواضح لمعاملة الري 80% من الاحتياج المائي الكلي وبشكل معنوي على معاملات الري الأخرى وخاصة على صفات الغلة الحبية وعدد الحبوب بالصف وعدد الحبوب بالكوز. تفوقت معاملتي الري 70% و80% وبشكل معنوي (4.52- 4.48كغ/م3 على الترتيب) بصفة كفاءة استخدام المياه وصفة نسبة التصافي (42.77 – 46.21 %) على الترتيب.